A case study of the links between strategy, innovation and internationalization in Portuguese SMEs - Barbosa, Fernando de Oliveira (2014)
Strategy formulation, innovation and internationalization, have strong relationships of mutual interdependence, and are widely referred to as decisive factors for the sustainable growth of SMEs. In this article we aim to study these relationships and their effects on business competitiveness, filling a gap in terms of the knowledge concerning these interactions, which is diffuse or inconclusive. Failure rates related to strategy, innovation and internationalization are high, with correspondingly high costs for companies, and we postulate that they are linked to aspects of implementation. As companies enter or consider each one of these dimensions of the business, they will incur in increasing costs if there is a poor implementation of strategy, innovation and internationalization. However, despite their importance, many SMEs do not have structured processes of strategy, innovation and internationalization. This may be particularly true in micro, entrepreneurial enterprises, which are the subject of this study. The determination of the causes and determinants, as well as the tools that companies use in designing their processes of formulation and implementation of strategy, innovation and internationalization, are extremely important in order to identify the factors and determinants that have major impacts on business performance, and explain how these effects occur or act. The importance of this issue is increasing, namely at the European level, because the market in each country is generally too small to allow the return on the investment made in developing a new product, so internationalization comes as a natural path to follow, once the innovation process is properly consolidated, based on a coherent, visionary and sustainable strategy. Many new firms initiate their activity with an explicit eye on internationalization and products designed for foreign markets should be prepared to compete at a global scale, supported by a clear differentiation strategy. This article is a case study of fifteen Portuguese micro enterprises (less than ten employees). The share of micro enterprises in the total business sector in Portugal is approximately 95,59%. Entrepreneurship has been encouraged by several policies, and new firms, with new approaches and skills, have surged. Our sample includes new firms and firms that were created several years ago, and spans several sectors of activity. We will examine, in the light of the main literature about the issue and in a critical way, the strategy, innovation and internationalization processes of these firms, and interpret them under the assumption that implementation aspects are critical to their performance and hence to their survival in a hypercompetitive global industry. The results of the study provide the ground for the proposal of a diagnostic assessment tool, which aims at performing an enquiry into the firm’s existing methodologies and practices related to strategy, innovation and internationalization, and thus allowing a more rigorous and systematic interpretation of the interactions of those processes. The diagnostic tool provides the basis for the proposal of adequate approaches that the firm can implement to better coordinate those processes. This assessment tool may be applicable to more mature SMEs as well, helping organizations improving their strategy processes.